US stock market sensitivity to interest and inflation rates: a quantile regression approach. Issue 26 (2nd June 2016) - Jareño, Francisco; Ferrer, Román; Miroslavova, Stanislava
ABSTRACT: This article studies the sensitivity of the US stock market to nominal and real interest rates and inflation during the 2003–2013 period using quantile regression (QR). The empirical results show that the stock market has a significant sensitivity to changes in interest rates and inflation and finds differences across sectors and over time. Moreover, the effect of changes in both interest rates and inflation tends to be more pronounced during extreme market conditions, thus distinguishing expansion periods from recession periods.